National innovation capacity and the drivers of energy efficiency R&D in the OECD - Ashraf Galal Eid (16982736) (2025)
Achieving COP28′s target to double global energy efficiency improvements by 2030 requires understanding how environmental regulations and market forces jointly shape energy R&D investment. This paper examines how environmental policy stringency and oil prices affect energy efficiency research and development spending across OECD countries (1990–2022) using Method of Moments Quantile Regression (MMQR). We find that environmental policy stringency has increasingly positive effects at higher energy efficiency R&D investment quantiles, supporting Porter's Hypothesis. Contrary to the induced innovation hypothesis, oil price increases consistently depress energy efficiency R&D, suggesting that higher energy costs divert resources from innovation. Additionally, policy effectiveness varies significantly with countries' R&D capabilities; innovation leaders respond more strongly than laggards. These findings have important implications for decarbonization strategies. While stringent environmental policies can drive innovation, their success depends on protecting energy efficiency R&D budgets from oil price volatility and tailoring policies to national innovation capacities. Policy frameworks must shield long-term investments from short-term market pressures while addressing countries’ heterogeneous innovation capabilities. Other Information Published in: Economic Analysis and Policy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.eap.2025.05.033